Building construction machinery and equipment. Portable, hand-held, internal combustion engine-driven abrasive cutting machines. Safety requirements for cut-off machines for centre-mounted rotating abrasive wheels Part 1, (4th March 2020) - British Standards Institution,
No abstract available